Avian sarcoma-leukosis virus pol-endo proteins expressed independently in mammalian cells accumulate in the nucleus but can be directed to other cellular compartments. - Morris-Vasios, C (1988)
Eucaryotic expression vectors have been used to study transient expression of the avian sarcoma-leukosis retrovirus pol-endo protein in COS cells. The constructs encode proteins with N termini identical to that of authentic viral pp32 endonuclease with the exception of a single met residue encoded by the initiator AUG. The C termini correspond to unprocessed viral pol protein, authentic processed pp32, or a derivative which includes eight amino acids from the unprocessed portion. All three proteins localize to the nucleus. However, when the pol-endo domain is fused to a secretory signal peptide, the protein is found in medium and appears also to localize in the Golgi bodies and the cell membrane. These and derivative vectors will make it possible to assess the consequence of retroviral pol gene expression in eucaryotic cells.